State’s fiduciary obligations concerning indigenous peoples and their territories: Using comparative law to propose solutions to conflicts that arise from extractive industries in Peru - Liendo Tagle, Fernando (2018)
Social and environmental conflicts arising from extractive activities in the lands of indigenous  peoples is a subject that has been analysed across various disciplines. This article does not attempt to weigh a comprehensive overview of the problem, but rather proposes an alternative legal analysis by employing comparative law and aspects of legal theory. In particular, this article will explore the doctrine of ‘fiduciary obligations’ in the context of the State’s relationship with indigenous peoples - focusing on the protection of the ownership of indigenous lands and the legal and administrative processes of the State – to evaluate whether the context, order and basis of the State’s fiduciary position can provide solutions in a Peruvian context.